Profil Iklim Mikro pada Budidaya Tanaman Kopi Robusta di Politeknik Negeri Jember - Wilujeng, Elly Daru Ika; Pertami, Rindha Rentina Darah; Rahma, Sinta Dwi; Firmansyah, Ahmad Fahim (Agropross : National Conference Proceedings of Agriculture, 2023)
Plant microclimate is the condition around plant from roots up to the top of canopy or up to 2 meters above the object. Microclimate is influenced by solar energy that received by the atmosphere, soil surface, and physical environment that exists on the land surface. The purpose of this study was to determine profile of microclimate in coffee cultivation that compared to open land in Jember State Polytechnic. The research was conducted on 03-05 March 2023. Observations included soil temperature, air temperature, and air humidity which were carried out at 3 times; in the morning (07.00-08.00), afternoon (12.00-13.00), and evening (17.00-18.00). The results showed that the soil temperature in coffee plantations had temperatures of 27.6 oC, 29.2 oC, and 26.9 oC, while in open land had temperatures 29 oC, 33.7 oC, and 28.7 oC. Analysis the air temperature was consecutive 29.2 oC, 34.5 oC, and 26.7 oC while in the open field, the air temperature was 30.2 oC, 39.7 oC, and 27.6 oC. Air humidity values ​​in Robusta coffee plantations were 78.8%, 51,3%, and 90.1% respectively, while in open land 75,5%, 87.5%, and 99%. Thus it can be concluded that the soil and air temperature of two fields have a trend increasing temperature during the day and decreasing in the afternoon, while the humidity in has decreased during the day and rises again in the afternoon, in contrast to observations of air humidity in open land the tren increase from morning to evening